2008
DOI: 10.1074/jbc.m801160200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FRA1 and FRA2 as Genes Involved in Regulating the Yeast Iron Regulon in Response to Decreased Mitochondrial Iron-Sulfur Cluster Synthesis

Abstract: The nature of the connection between mitochondrial Fe-S cluster synthesis and the iron-sensitive transcription factor Aft1 in regulating the expression of the iron transport system in Saccharomyces cerevisiae is not known. Using a genetic screen, we identified two novel cytosolic proteins, Fra1 and Fra2, that are part of a complex that interprets the signal derived from mitochondrial Fe-S synthesis. We found that mutations in FRA1 (YLL029W) and FRA2 (YGL220W) led to an increase in transcription of the iron reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
262
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(281 citation statements)
references
References 34 publications
16
262
1
Order By: Relevance
“…On the other hand, it was reported that Grx-BolA couples from various sources could also form apo-heterodimers (7,9). This is consistent with the observation that an in vivo Grx3/4-Fra2 interaction is found both in iron-replete and iron-depleted yeast cells (5).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…On the other hand, it was reported that Grx-BolA couples from various sources could also form apo-heterodimers (7,9). This is consistent with the observation that an in vivo Grx3/4-Fra2 interaction is found both in iron-replete and iron-depleted yeast cells (5).…”
supporting
confidence: 78%
“…The only characterized physiological role for a GrxBolA holo-heterodimer is in sensing the intracellular iron/Fe-S cluster status in yeast. The current model is that a complex formed by Fra1, Fra2, Grx3, and Grx4 links the mitochondrial Fe-S or iron status to the control of a set of genes involved in iron uptake, transport, and storage known as the iron regulon via the regulation of Aft1 transcription factor (5). Under irondeficient conditions, Aft1 is concentrated in the nucleus and activates the iron regulon, whereas under iron-sufficient conditions it is found predominantly in the cytoplasm.…”
Section: Rieske-type [2fe-2s] Coordination Occurs In Grx-bola_hmentioning
confidence: 99%
See 1 more Smart Citation
“…Aft1 is an activator, and in contrast, S. pombe Php4 is a repressor; however, both are active under conditions of iron deficiency and inactive in the presence of iron. Recent studies have provided clues with respect to irondependent inhibition of Aft1 (31)(32)(33)(34)62). One aspect is the requirement of the monothiol glutaredoxins Grx3 and Grx4 to allow Aft1 to sense iron excess (32,33).…”
Section: Grx4 Is Required For Iron Inhibition Of Php4 Activity In Smentioning
confidence: 99%
“…Elegant studies have also determined that S. cerevisiae monothiol glutaredoxins Grx3 and Grx4 are key regulators of Aft1 (32,33). When cells undergo a transition from iron-limiting to iron-sufficient conditions, it has been proposed that Grx3 and Grx4, with the aid of Fra1 and Fra2, transmit an as-yet-unidentified mitochondrial inhibitory signal, which contributes to inactivate Aft1 (32)(33)(34).…”
mentioning
confidence: 99%